Neurological, neurobehavioral, and radiological alterations in patients with mucopolysaccharidosis III (Sanfilippo's syndrome) in Brazil - Valle, Daniel Almeida do; Santos, Mara Lúcia Schmitz Ferreira; Telles, Bruno Augusto; Cordeiro, Mara L. (Frontiers in Neurology, 2022)
Mucopolysaccharidosis type III (MPS III) or Sanfilippo syndrome is the most common form of MPS. Although there is prominent neurological involvement in all stages of the disease. The current study aimed to comprehensively describe the neurological profile of children and adolescents with MPS III who visited the largest pediatric hospital in South America. A prospective/retrospective cohort analysis was performed on ten patients with MPS III from eight unrelated families. Most patients had achieved developmental milestones within the expected range for their age. Behavioral symptoms were reported in seven patients. All but two patients developed profound intellectual disabilities; 57% had epilepsy, and of these, 75% had their first seizure between 2 and 4 years of age; the frequency increased with age. Monotherapy was effective in 60% of patients. Two patients, both aged <8 years, had normal baseline electroencephalographic activity. Epileptiform activity was observed in three patients. Cortical atrophy has already been visualized on magnetic resonance imaging in 71% patients; all but one of these patients were aged >6 years. Neurological abnormalities increased in prevalence and severity with age. Drug resistance was uncommon. Dysmorphological and systemic manifestations were uncommon and mild, and did not correlate with neurological involvement. Despite high allelic heterogeneity, neurodegeneration was similar in the same group. These data contribute to the scarce literature from developing countries.